2013
DOI: 10.1016/j.juro.2012.09.166
|View full text |Cite
|
Sign up to set email alerts
|

Lymphopenia is an Independent Predictor of Inferior Outcome in Clear Cell Renal Carcinoma

Abstract: Purpose Low absolute lymphocyte count (ALC), a likely index of poor systemic immunity, may be associated with aggressive features and inferior survival in clear cell renal cell carcinoma (CCRCC). Materials and Methods We retrospectively analyzed preoperative blood cell counts in 430 patients (mean age 60 years) undergoing primary surgical resection for CCRCC at Fox Chase Cancer Center. ALC values as a continuous variable and at a level below 1300/μl (our lowest reference value) were correlated with nuclear g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
99
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 29 publications
2
99
0
11
Order By: Relevance
“…Although neutrophils are considered to be the first line of defense against infections, lymphocytes have been reported to play a crucial role in tumor defense by inducing cytotoxic cell death and inhibiting tumor cell proliferation and migration in the tumor microenvironment [28]. In addition, the prognostic value of lymphopenia has been demonstrated in nonhematopoietic malignancies, including pancreatic cancer, esophageal cancer, colorectal cancer, and renal cell carcinoma [29-32]. In fact, the present study demonstrated that DCC patients with low lymphocyte count, high NLR, high PLR, and low LMR tended to have worse prognosis, indicating a direct influence of lymphopenia on tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Although neutrophils are considered to be the first line of defense against infections, lymphocytes have been reported to play a crucial role in tumor defense by inducing cytotoxic cell death and inhibiting tumor cell proliferation and migration in the tumor microenvironment [28]. In addition, the prognostic value of lymphopenia has been demonstrated in nonhematopoietic malignancies, including pancreatic cancer, esophageal cancer, colorectal cancer, and renal cell carcinoma [29-32]. In fact, the present study demonstrated that DCC patients with low lymphocyte count, high NLR, high PLR, and low LMR tended to have worse prognosis, indicating a direct influence of lymphopenia on tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several studies also have shown that decreased preoperative LC was related to poor prognosis in various types of cancers including pancreatic cancer [10], esophageal cancer [11], renal cancer [12], and sarcoma and lymphoma [15]. Lymphocytes include CD4 + and CD8 + T cells, natural killer (NK) cells, NKT cells, gamma-delta T cells, and B cells, which are reported to be closely associated with tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Functional impairment of lymphocytes and decreased lymphocyte counts (LCs) have been reported in various types of cancers [8, 9]. Preoperative lymphopenia is reportedly associated with poor prognosis in several cancers [10-12], and this indicates that preoperative lymphopenia may reflect impaired host anticancer defense mechanisms. However, we previously reported that a rapid and significant decrease in total lymphocyte numbers was observed after surgery for GC [13].…”
Section: Introductionmentioning
confidence: 99%
“…The results from a recently published meta-analysis indicated that a high pre-treatment NLR was significantly related to poorer OS and PFS [23]. Recent studies also evaluated the correlation between inflammation and tumour response to chemotherapy in various tumour types [24][25][26]. Lissoni et al suggested that a decreasing lymphocyte count during chemotherapy might be correlated with tumour progression.…”
Section: Introductionmentioning
confidence: 99%